THU0537 Persistence and Dose Escalation of Tumor Necrosis Factor (TNF)-Blockers in us Veterans. (23rd January 2014) - Cannon, G. W.; DuVall, S. L.; Hayden, C.; Caplan, L.; Curtis, J. R.; Michaud, K.; Mikuls, T.; Reimold, A.; Collier, D. H.; Harrison, D. J.; Joseph, G. J.; Sauer, B.
Abstract : Background: Comparison of adalimumab (ADA), etanercept (ETN), and infliximab (INF) use in clinical practice may provide important insight into the comparative effectiveness and cost of approved therapies. Objectives: To examine persistence, dose escalation, clinical outcomes, and treatment costs with ADA, ETN, and INF for patients (pts) enrolled in the US Veterans Affairs RA (VARA) registry. Methods: VARA links to VA pharmacy and administrative databases, and documents longitudinal assessments of disease activity and outcomes. VARA pts initiating ADA, ETN, or INF from 3/18/2003 to 9/30/2010 were identified with follow-up data collected for ≥12 months. This analysis was limited to first treatment course beginning ≥180 days after VARA enrollment. A treatment course was defined as continuous medication dispensing in the absence of ≥90-day gap. Dose escalation was ≥25% increase in weekly dose. Cost was determined by drug costs alone and including drug administration (dispensing/infusion costs). Results: Data from 563 pts (204 ADA; 290 ETN; 69 INF) were analyzed (Table). No differences in persistence were seen (Fig A). Dose escalation was most common with INF followed by ADA (Fig B). Persistence post-escalation was similar for all agents. Mean DAS28 and change in DAS28 in 61 evaluable pts were similar for each drug. Average annual costs were highest for INF. Image/graph: Conclusions: In VARA, persistence on ADA, ETN and INF was similar. Escalation was most common with INF and least frequent with ETN, and did not impact persistence. Drug costs were higher for INF than ADA and ETN. Persistence and DAS scores were similar regardless of dose escalation. Acknowledgements: Research funded by VA Research Program and Immunex Corporation, a wholly owned subsidiary of Amgen Inc., and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: G. Cannon Grant/research support from: Amgen Inc., S. DuVall Grant/research support from: Amgen Inc, Anolinx LLC, Genentech Inc, F. Hoffmann-La Roche Ltd, Merck & Co Inc, Mylan Specialty LP, and Shire PLC, C. Hayden: None Declared, L. Caplan: None Declared, J. Curtis Grant/research support from: Roche/Genentech, UCB, Centocor, CORRONA, Amgen, Pfizer BMS, Janssen, AbbVie, K. Michaud: None Declared, T. Mikuls Grant/research support from: Genentech/Roche, A. Reimold Grant/research support from: Lilly, Novartis, Janssen, Ardea, Consultant for: UCB, D. Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Harrison Shareholder of: Amgen Inc., Employee of: Amgen Inc., G. Joseph Shareholder of: Amgen Inc., Pfizer Inc., Employee of: Amgen Inc., B. Sauer Grant/research support from: Amgen Inc.